The Oxford Handbook of Systematic Theology - Webster,John . Tanner,Kathryn. Torrn, Iain (Oxford ; New York Oxford University Press, 2007)
A set of original and authoritative accounts, by an distinguished international team of authors, of all the major areas of current research in Christian systematic theology, offering a thorough survey of the state of the discipline and of its prospects fo
Keywords: Theology, Doctrinal. Systematische theologie. Systematische Theologie